THE CASE FOR A BALANCED BUDGET CONSTITUTIONAL PROVISION IN GHANA - Amponsah, Nicholas (European Scientific Journal, ESJ, 2014)
Fiscal indiscipline has been a major tussle of most African nations and a disturbing problem. How African governments and the people can subscribe to the basic principles and canons of institutional restraint and accountability which are hallmarks of good governance and subscribe to the basic principles and canons of institutional restraint and accountability which are hallmarks of good governance, has continued to challenge us. The paper attempts to provide some reasons for the menace and some mechanisms for resolution.